O Arquivo Universitário e as suas diretrizes: um estudo de caso do Sistema de Arquivo da Unicamp (SIARQ) - Geronimo, Michele Brasileiro [UNESP] (2014)
The archival standards back up the records management in a university, once they settle procedures which standardize documents’ production and processing; thus, they are such a tool within an institution, mainly regarding a records/archives system. This way, we establish this study’s problem towards the fact that in universities such an amount of documents come out, once they are complex environments, bringing about constant flow of documents. For such reason, standardizing aims at guiding archival procedures for bringing liability and effectiveness upon the institution’s records activities. In this sense, the instructions regarding the records management and the University Records are what we are mostly focused on this investigation. We present a discussion about the rules concerning the production and processing of documents in Campinas State University Records/Archives System (SIARQ/UNICAMP). The general objective of this study is fairly discussing and analyzing the rules about the production and processing of documents at SIARQ/UNICAMP. The research is qualitative and we have used the descriptive case study, aiming at specifically analyzing the archival standards application referring to the production and processing of documents within a university context, standing out the importance and influence os such rules in an archival institution. We now conclude that the institution makes out the standardization establishment importance, once it does approach the production and processing of documents throughout the university. Such position backs up the effort for its settling through the environments which constitute the institution. It has been possible to demonstrate such rules happen-making will depend on the organization’s culture. As it is a records/archives system, such factor may vary.